2004
DOI: 10.1103/physrevlett.92.237202
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Study of Ferromagnetism in Epitaxial Si-Mn Thin Films on Si(001)

Abstract: Density-functional theory calculations are employed to investigate both the epitaxial growth and the magnetic properties of thin Mn and MnSi films on Si(001). For single Mn adatoms, we find a preference for the second-layer interstitial site. While a monolayer Mn film is energetically unfavorable, a cappingSi layer significantly enhances the thermodynamic stability and induces a change from antiferromagnetic to ferromagnetic order. For higher Mn coverage, a sandwiched Si-Mn thin film (with CsCl-like crystal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
69
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 21 publications
7
69
1
Order By: Relevance
“…20 In this study, Mn was found to be incorporated into Si as an interstitial dopant in good agreement with recent first-principles calculations. [23][24][25] The interstitial Mn was also observed in thin films irradiated by ultraviolet light releasing metal species into the semiconductor substrate. 26 Meanwhile, molecular beam epitaxy produces samples with mostly substitutional Mn in the Si matrix.…”
Section: Introductionmentioning
confidence: 90%
“…20 In this study, Mn was found to be incorporated into Si as an interstitial dopant in good agreement with recent first-principles calculations. [23][24][25] The interstitial Mn was also observed in thin films irradiated by ultraviolet light releasing metal species into the semiconductor substrate. 26 Meanwhile, molecular beam epitaxy produces samples with mostly substitutional Mn in the Si matrix.…”
Section: Introductionmentioning
confidence: 90%
“…In order to circumvent these problems we are investigating the feasibility of a surface-driven approach for the incorporation of Mn into a Si matrix. This approach has been suggested in several theoretical studies, which indicate that selected Mn-Si surface structures, and delta-doped layers of Mn embedded in Si might indeed be ferromagnetic [11,[16][17][18][19][20][21][22][23]. A set of recent STM studies has been geared towards the investigation of the formation of Mn surface structures on the Si(1 0 0) surface [18][19][20]24].…”
Section: Introductionmentioning
confidence: 99%
“…The case where the sp atom comes from the IVth column of the periodical table has attracted much less attention in literature and to the best of our knowledge only the cases of MnC [8,9,10], MnSn [9] and MnSi [11,12,13] in the zincblende lattice have been studied. In this manuscript we study using the full-potential nonorthogonal local-orbital minimum-basis band structure scheme (FPLO) [14] within the local density approximation (LDA) [15] the case of [Sc 1−x V x ]C and [Sc 1−x V x ]Si alloys for x taking the values 0, 0.1, 0.2, ...,0.9, 1.…”
Section: Introductionmentioning
confidence: 99%